Before night falls - Gray, Keith (Eddinburg : Barrington Stoke, 2006)
When Andy sets off on a camping with three friends, he has only one thing in mind. He wants to spend some quality time with his girlfriend, Lucy, with no parents around. but things do not go according to plan. It's wet and cold. They are soaked and lost.... and than Lucy wanders off on her own. She's found alive several hours later, but with strange marks on her neck. Could she have been bitten by a vampire? Their trip is fast turning into a nightmare and things are going from bad to worse..
Keywords: Mystery -- Fiction; Vampire -- Fiction